Let’s talk care : a communications campaign to promote advance care planning (ACP) in Singapore - Chew, Esther Pei Ting (2019)
This paper presents ‘Let's Talk Care’, a health communication campaign that aims to raise awareness about Advance Care Planning (ACP) in Singapore among Singaporeans aged 50 to 64 who do not have any life-threatening illnesses. The campaign is conceptualised and executed by four final-year undergraduate students from the Wee Kim Wee School of Communication and Information, Nanyang Technological University. ACP is a process where individuals plan and share their future care preferences with their loved ones and/or healthcare providers, in the event that he/she loses the mental capacity to make his/her own decisions. ACP helps to simplify the decision-making process for family members and medical professionals and facilitates better end-of-life care outcomes for the individual. The team’s formative research found that there is a general lack of awareness about ACP. Guided primarily by the Theory of Planned Behaviour, the campaign aimed to increase the target audience’s intentions to do ACP, through the campaign’s key message of planning for one’s care benefits one’s loved ones. Some key tactics include producing profile-led videos, a reflection workbook, and holding roving booths at various community and healthcare locations. A post-campaign evaluation was done through measuring our output and analysing post-campaign survey results against our impact objectives. Results showed that attitudes, subjective norms and actual behaviour were influenced by the campaign, with most output objectives achieved. The paper also discusses the campaign’s strengths and limitations, and future efforts for ACP campaigns.